2001
DOI: 10.2337/diacare.24.4.710
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glycemic Control and Enhanced Insulin Sensitivity in Type 2 Diabetic Subjects Treated With Pioglitazone

Abstract: OBJECTIVE -To elucidate the effects of pioglitazone treatment on glucose and lipid metabolism in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS -A total of 23 diabetic patients (age 30 -70 years, BMI Ͻ 36 kg/m2 ) who were being treated with a stable dose of sulfonylurea were randomly assigned to receive either placebo (n ϭ 11) or pioglitazone (45 mg/day) (n ϭ 12) for 16 weeks. Before and after 16 weeks of treatment, all subjects received a 75-g oral glucose tolerance test (OGTT); and hepatic and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
253
3
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(291 citation statements)
references
References 46 publications
28
253
3
5
Order By: Relevance
“…That would be consistent with our finding that troglitazone treatment of human muscle cells, besides increasing glucose uptake, increased glycogen synthase activity and glucose incorporation into glycogen (52). This would also be consistent with the results of Miyazaki et al (45), who reported that the increase in whole body glucose disposal following pioglitazone treatment of diabetic subjects could be accounted for by the increase in nonoxidative glucose metabolism, usually taken to represent glycogen synthesis.…”
Section: Discussionsupporting
confidence: 82%
“…That would be consistent with our finding that troglitazone treatment of human muscle cells, besides increasing glucose uptake, increased glycogen synthase activity and glucose incorporation into glycogen (52). This would also be consistent with the results of Miyazaki et al (45), who reported that the increase in whole body glucose disposal following pioglitazone treatment of diabetic subjects could be accounted for by the increase in nonoxidative glucose metabolism, usually taken to represent glycogen synthesis.…”
Section: Discussionsupporting
confidence: 82%
“…Although PPARγ agonists reduce both fasting and postprandial glucose [38,39], these agents may be less effective in postprandial glucose reduction compared with other hypoglycemic agents [40]. In our data, whereas fasting glucose level decreased, postprandial glucose level did not decline significantly.…”
Section: Discussionmentioning
confidence: 31%
“…TZDs decrease insulin resistance and improve insulin action, thus ameliorating glycemic control and reducing circulating insulin concentrations. 20,21 Inflammatory cells in human atheroma express PPAR␥, 22,23 and PPAR␥ agonists exert antiinflammatory functions in vitro. 24 Thiazolidinediones can reduce inflammation, as indicated by diminished serum levels of CRP in patients with type 2 diabetes.…”
mentioning
confidence: 99%